A review on recent advancements in photocatalytic remediation for harmful inorganic and organic gases. (December 2021) - Priya, A.K.; Suresh, R.; Kumar, P. Senthil; Rajendran, Saravanan; Vo, Dai-Viet N.; Soto-Moscoso, Matias
Abstract: Due to the continuous increase in industrial pollution and modern lifestyle, several types of air contaminants and their concentrations are emerging in the atmosphere. Besides, photocatalysis has gained much attention in the elimination of air pollution. Several ultraviolet and visible light active photocatalysts were tested in air pollutant treatment and thereby, the number of reports was increased in the past few years. In this context, this review describes the photocatalytic treatment of gaseous inorganic contaminants like NOx, H2 S, and organic pollutants like formaldehyde, acetaldehyde, and benzene derivatives. Different photocatalysts with their air pollutant removal efficiency were explained. Improving strategies such as metal/non-metal doping, composite formation for photocatalyst activities have been studied. Moreover, an analysis is presented from each of the existing photocatalytic immobilization approaches. Also, factors responsible for effective photocatalysis were explained. Overall, the photocatalytic abatement technique is an auspicious way to eliminate different air contaminants. Besides, existing drawbacks and future challenges are also discussed. Graphical abstract: Image 1 Highlights: Photocatalysis has vital role in air pollution removal. Various photocatalyst immobilization methods on support were mentioned. Toxicity of inorganic gases can be reduced through photocatalytic conversion. Aliphatic and aromatic gaseous pollutants can be mineralized by photocatalysis.